Serum cortisol levels and neuropsychological impairments in patients diagnosed with Fibromyalgia - Barcelo Martinez, Ernesto (2018)
Objective. To describe the relationship between neuropsychological variables and serum cortisol levels as a measure of physiological stress in patients with fibromyalgia.Methodology. A sample of 60 women was intentionally selected: 30 with Fibromyalgia diagnosis and 30 with normal controls. Cortisol levels were determined using two blood samples (AM and PM) and a neuropsychological and emotional battery was applied with a standardized protocol in Colombian population to evaluate different cognitive domains. Comparative and correlational non-parametric analyzes were performed, a multiple regression analysis to determine influences between variables.Results. Significant differences between the study groups in the neuropsychological variables (attention, memory, language, visual-constructive praxis and executive functions (EF), (p<0.05) were found, obtaining better scores in the control group. Significant correlations between the cortisol profile, with false acknowledgments of Rey auditory-verbal learning test, and with perseverative errors of the Wisconsin test were found. Multiple regression analysis predicts the influence of memory and EF variables on the cortisol profile in an 88.7%.Conclusions. The findings show that, in patients with FM, there are neuropsychological alterations, mainly in executive functioning (cognitive flexibility) and episodic memory (evocation and storage). Likewise, executive dysfunction is related to physiological stress reciprocally and in turn areconditioned by emotional alterations such as symptoms of depression, which supports the neurophysiological model that compromises the hypothalamic-pituitary-adrenal axis and the prefrontal cortex, rich in corticosteroid receptors.